Do galectins serve as soluble ligands for immune checkpoint receptors? - Torres, Nicolás (2024)
Galectins are a family of soluble glycan-binding proteins containing one or two highly conserved carbohydrate recognition domains (CRDs) that preferentially bind to lactosamine (LacNac; Galβ1-4NAcGlc) structures present on different cell surface receptors and the extracellular matrix. Unlike other lectins such as C-type lectin receptors and sialic acid-binding immunoglobulin-type lectins (Siglecs), which are mostly transmembrane proteins, galectins are synthesized as cytosolic proteins, reside in the cytosol or nucleus for much of their lifetime, and are released into the extracellular medium through non-classical secretory mechanisms bypassing the endoplasmic reticulum (ER)-Golgi system.